2017
DOI: 10.1016/j.ophtha.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Relative Genetic and Environmental Contributions to Variations in Human Retinal Electrical Responses Quantified in a Twin Study

Abstract: PurposeTo estimate heritability of parameters of human retinal electrophysiology and to explore which parameters change with age.DesignProspective, classic twin study.ParticipantsAdult monozygotic and dizygotic twin pairs recruited from the TwinsUK cohort.MethodsElectroretinogram responses were recorded using conductive fiber electrodes in response to stimuli incorporating standards set by the International Society for the Clinical Electrophysiology of Vision. These parameters were extracted; in addition, phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…As ERG parameters from both twins of a given pair are highly correlated [14], only one twin from each pair was included for subsequent analysis. As ERG parameters vary with age [14, 15], the two groups were age-matched by ensuring the same numbers of participants in each age decade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ERG parameters from both twins of a given pair are highly correlated [14], only one twin from each pair was included for subsequent analysis. As ERG parameters vary with age [14, 15], the two groups were age-matched by ensuring the same numbers of participants in each age decade.…”
Section: Methodsmentioning
confidence: 99%
“…As ERG parameters vary with age [14, 15], the two groups were age-matched by ensuring the same numbers of participants in each age decade. This resulted in 28 participants per group.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we investigated recordings obtained previously from 211 adult participants from the TwinsUK cohort (with ages ranging from 23 to 86 years) who underwent ISCEV standard recording of ERGs. The primary aim at the time of the recordings had been to investigate heritability of response parameters and investigate factors such as correlation with age 12 ; no recordings were excluded on the basis of waveform shape or relative amplitudes of waveform components. We found that, in response to international standard stimuli, no participant Open access had an electronegative waveform.…”
Section: Discussionmentioning
confidence: 99%
“…Adult participants were recruited from the TwinsUK cohort, 12 which is a registry of largely healthy adult twins, who have volunteered to participate in research studies at St Thomas’ Hospital, London. 13 Participants underwent full-field ERG testing which incorporated the ISCEV standard protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation